(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Head & Neck lesions encompass a multitude of congenital, inflammatory or neoplastic lesions including several anatomic sites and originating in different tissues and organs. FNAC is a simple, quick, feasible, cost effective and repeatable outpatient procedure with minimum risk of complications. Objective: The purpose of the present study was to study the spectrum of head & neck lesions attending in outpatient. Methodology: This present cross-sectional study included the patients presented with palpable head & neck swelling from January 2018 to September 2019 in outpatient (mostly ENT & HNS OPD) department of Monno Medical College & Hospital, Monno City, Gilondo, Manikgonj. Aspirates were done using mostly 5ml syringe and 23-gauge needle. Smears were stained with Papanicolaou stain. Results: Out of 210 patients of head & neck lesions studied, Lymph node (50.47%) was the predominant site aspirated with chronic nonspecific lymphadenitis & lymphoid hyperplasia being the commonest lesion. Thyroid lesions constituted 31.90% cases followed by soft tissue (11.9%) and salivary gland (5.71%). Conclusion: In conclusion FNAC is simple, quick, inexpensive and minimally invasive technique to diagnose different types of head and neck swelling. It could differentiate the infective process from neoplastic one and avoid unnecessary surgeries. Journal of Current and Advance Medical Research, January 2021;8(1):21-24